Stakeholders' perspectives on the regulation and integration of complementary and alternative medicine products in Lebanon: a qualitative study - Alameddine, Mohamad (BioMed Central, 2011)
BACKGROUND: The regulation of the markets for Complementary and Alternative Medicine (CAM) products presents a global challenge. There is a dearth of studies that have examined or evaluated the regulatory policies of CAM products in the Eastern Mediterranean Region (EMR). We investigate the regulatory frameworks and the barriers for the proper regulation and integration of CAM products in Lebanon, as an example of an EMR country with a weak public infrastructure. METHODS: We utilized a qualitative study design involving a series of semi-structured interviews with stakeholders of the CAM market in Lebanon. Snowball sampling was used to identify interviewees; interviews continued until the "saturation" point was reached. A total of 16 interviews were carried out with decision makers, representatives of professional associations, academic researchers, CAM product importers, policy makers and a media representative. Interviews were transcribed and thematic analysis of scripts was carried out. RESULTS: There was a consensus among all stakeholders that the regulation of the market for CAM products in Lebanon needs to be strengthened. Thematic analysis identified a number of impediments jeopardizing the safety of public consumption and hindering the integration of CAM therapies into mainstream medicine; including: weak infrastructure, poor regulation, ineffective policies and politics, weak CAM awareness and sub-optimal coordination and cooperation among stakeholders. With respect to policy instruments, voluntary instruments (self regulation) were deemed ineffective by stakeholders due to poor awareness of both users and providers on safe use of CAM products. Stakeholders' rather recommended the adoption of a combination of mixed (enhancing public awareness and integration of CAM into medical and nursing curricula) and compulsory (stricter governmental regulation) policy instruments for the regulation of the market for CAM products. CONCLUSIONS: The current status quo with respect to the regulation of CAM products in Lebanon is not conducive to public safety, nor does it support the integration of CAM products into the healthcare system. The Ministry of Health indeed plays a dominant role in the regulation of these products through a combination of mixed and compulsory policy instruments. Yet, the proper implementation of these regulations requires political resolve coupled with the cooperation of all CAM stakeholders.